Quadruple adenine base–edited allogeneic CAR T cells outperform CRISPR/Cas9 nuclease–engineered T cells - Nils W. Engel; Israel Steinfeld; Daniel Ryan; Kusala Anupindi; Samuel Kim; Nils Wellhausen; Linhui Chen; Katherine Wilkins; Daniel J. Baker; Philipp C. Rommel; Danuta Jarocha; Mercy Gohil; et al. (Proceedings of the National Academy of Sciences, 2025)
Genome-editing technologies have enabled the clinical development of allogeneic cellular therapies, yet the optimal gene-editing modality for multiplex editing of therapeutic T cell product manufacturing remains elusive. In this study, we conducted a comprehensive comparison of CRISPR/Cas9 nuclease and adenine base editor (ABE) technologies in generating allogeneic chimeric antigen receptor (CAR) T cells, utilizing extensive in vitro and in vivo analyses. Both methods achieved high editing efficiencies across four target genes, critical for mitigating graft-versus-host disease and allograft rejection: TRAC or CD3E , B2M , CIITA , and PVR . Notably, ABE demonstrated higher manufacturing yields and distinct off-target profiles compared to Cas9, with translocations observed exclusively in Cas9-edited products. Functionally, ABE-edited CAR T cells exhibited superior in vitro effector functions under continuous antigen stimulation, including enhanced proliferative capacity and increased surface CAR expression. Transcriptomic analysis revealed that ABE editing resulted in reduced activation of p53 and DNA damage response pathways at baseline, along with sustained activation of metabolic pathways during antigen stress. Consistently, Assay for Transposase-Accessible Chromatin using sequencing data indicated that Cas9-edited, but not ABE-edited, CAR T cells showed enrichment of chromatin accessibility peaks associated with double-strand break repair and DNA damage response pathways. In a preclinical leukemia model, ABE-edited CAR T cells demonstrated improved tumor control and extended overall survival compared to their Cas9-edited counterparts. Collectively, these findings position ABE as superior to Cas9 nucleases for multiplex gene editing of therapeutic T cells.